2009
DOI: 10.1007/s10827-009-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Variability of bursting patterns in a neuron model in the presence of noise

Abstract: Spiking and bursting patterns of neurons are characterized by a high degree of variability. A single neuron can demonstrate endogenously various bursting patterns, changing in response to external disturbances due to synapses, or to intrinsic factors such as channel noise. We argue that in a model of the leech heart interneuron existing variations of bursting patterns are significantly enhanced by a small noise. In the absence of noise this model shows periodic bursting with fixed numbers of interspikes for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 67 publications
(98 reference statements)
1
24
0
Order By: Relevance
“…7(c1)]. This is similar to neuronal bursting models perturbed by noise [36]. The variability of the number of spikes in a burst is reflected in a broad peak at low frequency, corresponding to the bursting period and its higher harmonics.…”
Section: Effect Of the Met Current Fluctuations: Stochastic Dynamicsmentioning
confidence: 63%
See 1 more Smart Citation
“…7(c1)]. This is similar to neuronal bursting models perturbed by noise [36]. The variability of the number of spikes in a burst is reflected in a broad peak at low frequency, corresponding to the bursting period and its higher harmonics.…”
Section: Effect Of the Met Current Fluctuations: Stochastic Dynamicsmentioning
confidence: 63%
“…A zoom of the bifurcation diagram in Fig. 4(b) reveals that each subsequent spike adding is accompanied by chaotic bursting within a narrow parameter window, in a manner similar to neuronal models [30,31,3436]. Near the terminal point of the spike adding cascade the model generates unpredictably long bursting trains with chaotically alternating numbers of spikes [Fig.…”
Section: Deterministic Dynamicsmentioning
confidence: 89%
“…Also, it was shown that the noise in the dendrites has a large effect on the spike precision (van Rossum et al 2003). Also, the bursting patterns vary substantially in the presence of noise (Channell et al 2009). Our model can be extended to explore underlying mechanisms of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Phase reduction, for example, is not applicable in the analysis of stability of burster networks that are strongly coupled. Conversely, random perturbations can effectively elucidate the dynamical stability of such systems that otherwise evade standard analysis methods [36]. Such systems also include those near bifurcations and those that are singularly perturbed [37,38].…”
Section: Introductionmentioning
confidence: 99%